Sistema de controle de acesso integrado com central de alarme - Rovani, Esequiel (2019)
The access control is a system used for managing people in a restricted location. The control is done through electronic equipment, enclosures and locks, where the user must be registered to access the environment. These systems are designed to meet property security requirements. In condominiums, there is a vulnerability in these systems, as most are limited only to opening and closing doors, and have no integration with an alarm system that generates notification to a monitoring company in case of intrusion. The present work presents the integration of two distinct security systems in a single central (alarm and access control), aiming to increase the security of condominium entrances, since today in the market there are equipaments that are distant in this aspect. The enclosure automation is done through an access control, which will manage the interlocking of the doors and release them by tag, Password, fire system firing and autonomous release by the building intercom system. The system also features intrusion detection by magnetic sensors. All of this is managed by a single switchboard, where it has outputs (dry contact) for integration with a data transmission device (GPRS or Internet) that sends trigger events to a monitoring switch